2018
DOI: 10.31466/kfbd.392106
|View full text |Cite
|
Sign up to set email alerts
|

Şeker İkamesi Olarak Stevya Estraktı Kullanımının Keklerin Bazı Fiziksel ve Duyusal Özellikleri Üzerine Etkisi

Abstract: Kekler tüm dünyada farklı formüllerle üretilebilen ve oldukça geniş bir tüketici kitlesi tarafından tüketilen ürünlerdir. Kek formülünde bulunan şekerin çeşitli fonksiyonel özellikleri vardır. Şeker enerji verdiğinden düşük kalorili ürün geliştirme amacı ile şeker ikameleri üzerine araştırmalar gerçekleştirilmektedir. Stevya özütü kullanımının bu tür ürünlerde meydana getireceği değişikliklere yönelik çalışmalarda artmaktadır. Bu çalışmada farklı oranlarda sıvı stevya özütü ilavesinin keklerin bazı kalite krit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
1
0
2
Order By: Relevance
“…Cıngoz and Demırdoven (2022) reported that, according to the sensory evaluation results of pumpkin marmalades prepared with four different recipes by adding spices, stevia, and granulated sugar in different proportions, granulated sugar-added pumpkin marmalades without spices received the highest scores, followed by stevia-added samples. In their study on the effect of usingcarob flour, stevia and cinnamon in the production of diabetic strawberry jam on the product's sensory properties, Mutlu et al (2021) reported that the control group (industrially produced traditional strawberry jam) had the highest average values according to the general acceptability scores. They also reported that the traditional strawberry jam produced with stevia + cinnamon had the closest mean values to the control group in terms of all parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Cıngoz and Demırdoven (2022) reported that, according to the sensory evaluation results of pumpkin marmalades prepared with four different recipes by adding spices, stevia, and granulated sugar in different proportions, granulated sugar-added pumpkin marmalades without spices received the highest scores, followed by stevia-added samples. In their study on the effect of usingcarob flour, stevia and cinnamon in the production of diabetic strawberry jam on the product's sensory properties, Mutlu et al (2021) reported that the control group (industrially produced traditional strawberry jam) had the highest average values according to the general acceptability scores. They also reported that the traditional strawberry jam produced with stevia + cinnamon had the closest mean values to the control group in terms of all parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Kek verimi ve pişme kaybı Palamutoğlu ve diğ. [11] tarafından tanımlanan metoda göre belirlenmiştir. Kek yüksekliği numuneler ortadan dikey olarak kesilerek ve en yüksek noktanın yüksekliği ölçülerek belirlenmiştir [5].…”
Section: Kalite öZelliklerinin Belirlenmesi 1) Besin öğEleri Kompozisyonuunclassified
“…Ülkemizde de stevya kullanılarak hazırlanan diyabetik reçel (Mutlu, Yalınkılıç & Mutlu, 2021), dondurma (Ozdemir vd. 2015), glutensiz bisküvi (Yıldız, 2019), kek (Palamutoğlu, Kasnak & Moral, 2018), meyve nektarı ve meyveli içecek (Yıldız & Karhan, 2021), meyve (kızılcık) pestili (Şengül & Ünver, 2022) vb. gıdalar üzerine çalışmalar bulunmaktadır.…”
unclassified